Le chant de Thyrsis dans l’Idylle I de Théocrite : des emprunts au Prométhée enchaîné ? - Mélanie Zammit (Aitia)
This paper considers the possibility that the character of Daphnis, as represented by Theocritus in Idyll 1, is partly inspired by the tragic Prometheus Bound, generally attributed to Aeschylus. The connection between the two characters has already been suggested by various critics and we explore the common points between the two characters, but also the links that can be made between the dramaturgy of the Prometheus Bound and the development of the song of Thyrsis. Finally, we go back to the entire tragic intertext that we can guess in Idyll 1 to try to understand how this poem presents a bucolic variation of tragic themes and motifs.